Legal Protection for Victims of Violence That Causes Investigators to Say They Flee from the Crime - Nasution, Ahmad Hafiz; Purba, Jesikapna; Harahap, Reza Ali; Alfatah, Ridho; Silalahi, Rizky Ananda; Aprilia, Zia Syariah; Fajriawati, Fajriawati (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The aim of this research is to find out how victims of violence are protected in the criminal justice system in Indonesia and how investigators act in terms of coercive actions. By using legal research methods, it can be concluded that: Although criminal law focuses directly on victims with compensation, it is still very limited and restrictive to court judges. According to the sentence, the judge can impose special requirements on the convict to compensate for all or part of the losses resulting from the crime. In the relevant circumstances, viz. If the interests of society are disturbed, based on the authority of the authorities, they can carry out coercive actions which actually harm a person's human rights according to Law no. 4 of 2004. Jurisdiction This part of the Law stipulates that no one may be arrested, detained, searched and arrested except based on a written order from a legal authority. determined by law.